"LEGÍTIMA DEFESA DA HONRA E OUTRAS LOUCURAS": A RELAÇÃO MÍDIA E SOCIEDADE ATRAVÉS DO SERIADO MALU MULHER - Clarissa de Souza Oliveira Godoy (TRF2, 2019)
This article examines the relationship between the mass media,specifically Brazilian television, and the Brazilian feminist movement in the late 1970s, when such movements were consolidating their patterns and demands in Brazil. It will be presented the representation of feminism in the series Malu Mulher, through the analysis of one of the chapters, seeking to understand the possibilities of contribution to the dissemination of the feminist movement and which current feminist became protagonist of the series. This analysis is based on the discussion of one of the main guidelines of the 1980s feminist movement that was domestic violence.